THE IMPACT OF GOVERNMENT POLICY, FINANCIAL LITERACY, MARKET ACCESS, AND INNOVATION ON THE GROWTH OF MSMES IN INDONESIA - Rifki Suwaji; Iwan Harsono (CV. Adiba Aisha Amira, 2025)
The multiple effects of financial literacy, market accessibility, government policy, and innovation on the expansion of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia are examined in this study. A thorough investigation of Structural Equation Modeling (SEM) with Partial Least Squares (PLS-SEM) was carried out on a sample of 250 different MSMEs. Each exogenous variable and MSME growth have strong and positive connections, according to the data. Government policy becomes evident as a potent motivator, highlighting the necessity of encouraging regulatory environments. Significant influences are also shown by financial literacy, market access, and innovation, highlighting the significance of a comprehensive strategy for promoting MSME growth. Policymakers, stakeholders, and MSME owners can use the findings to establish focused initiatives that foster an environment that is favorable to the sustainable development of MSMEs in Indonesia.